Cover Feature: Vacancy Engineering in Transition Metal Sulfide and Oxide Catalysts for Hydrodeoxygenation of Lignin‐Derived Oxygenates (ChemSusChem 20/2021). Issue 20 (29th September 2021) - Jiang, Sinan; Ji, Na; Diao, Xinyong; Li, Hanyang; Rong, Yue; Lei, Yaxuan; Yu, Zhihao
Abstract : The Cover Feature shows the vacancy engineering of transition metal sulfide and oxide catalysts, which effectively affect the hydrodeoxygenation of lignin‐derived oxygenates into high‐value chemicals, therefore providing new ideas for solving energy problems. More information can be found in the Minireview by S. Jiang et al .